Long Term Cognitive Function After Cardiac Arrest: A Mini-Review - Hagberg, Guri; Ihle-Hansen, Håkon; Sandset, Else Charlotte; Jacobsen, Dag; Wimmer, Henning; Ihle-Hansen, Hege (Frontiers in Aging Neuroscience, 2022)
Out-of-hospital cardiac arrest (OHCA) is a leading cause of mortality worldwide. With better pre- and inhospital treatment, including cardiopulmonary resuscitation (CPR) as an integrated part of public education and more public-access defibrillators available, OHCA survival has increased over the last decade. There are concerns, after successful resuscitation, of cerebral hypoxia and degrees of potential acquired brain injury with resulting poor cognitive functioning. Cognitive function is not routinely assessed in OHCA survivors, and there is a lack of consensus on screening methods for cognitive changes. This narrative mini-review, explores available evidence on hypoxic brain injury and long-term cognitive function in cardiac arrest survivors and highlights remaining knowledge deficits.